Clinical cure rate of inactive HBsAg carriers with HBsAg <200 IU/ml treated with pegylated interferon - Li, Hong; Liang, Shan; Liu, Lili; Zhou, Daqiong; Liu, Yali; Zhang, Yang; Chen, Xinyue; Zhang, Jing; Cao, Zhenhuan (Frontiers in Immunology, 2022)
Purpose HBsAg clearance represents clinical cure for patients with hepatitis B, but remains difficult to obtain for most HBV-infected patients. Recent studies have shown that inactive HBsAg carriers treated with pegylated interferon can achieve higher clinical cure rates, which may imply that the lower the baseline HBsAg quantification, the higher HBsAg clearance rate. Therefore, this study further investigated the HBsAg clearance rate in inactive HBsAg carriers with low level of HBsAg (<200 IU/ml) treated with pegylated interferon. Methods This is a prospective cohort study. Inactive HBsAg carriers with HBsAg<200 IU/ml were divided into treatment and control groups. Pegylated interferon was administered to the patients in therapeutic group for 96 weeks. The patients in control group underwent 96 weeks of observation without any anti-viral treatment. All patients were tested for HBsAg, anti-HBs, HBV DNA, liver function, blood count, thyroid function, thyroid antibodies and autoantibodies at baseline, week 12, 24, 36, 48, 60, 72, 84 and 96. Controlled attenuation parameter (CAP) and liver stiffness measure (LSM) were evaluated at baseline and week 96. Patients were classified into no steatosis, mild steatosis, moderate steatosis and severe steatosis according to the value of CAP. Results A total of 174 inactive HBsAg carriers with HBsAg<200IU/ml were enrolled, including 84 in the treatment group and 90 in the control group. In the treatment group, HBsAg clearance rate was 30.77% (24/78) at week 48, and increased to 57.69% (45/78) at week 96. HBsAg clearance occurred in 2 patients with a clearance rate of 2.27% (2/88) in control group, The HBsAg clearance rate of the treatment group was significantly higher than that of the control group (P<0.001). HBsAg clearance was significantly higher in patients with moderate steatosis than in those without steatosis (74.07% vs. 48.15%, p=0.008) at week 96. Conclusion High HBsAg clearance rate could be obtained for inactive HBsAg carriers with HBsAg< 200 IU/ml treated with peginterferons. Inactive HBsAg carriers with moderate hepatic steatosis are more sensitive for the treatment.